Effects of nasal continuous positive airway pressure compared with high flow nasal cannula on the coordination between swallowing and breathing in post-extubation patients, a randomized crossover study: Swallowing–breathing coordination with CPAP vs HFNC - Cowawintaweewat, Sawita; Kongpolprom, Napplika (Clinical Critical Care, 2025)
Background: Coordination between swallowing and breathing is essential to prevent aspiration. Swallowing during expiration (E-E swallow) is considered the most protective pattern [1,2]. High-flow nasal cannula (HFNC) and continuous positive airway pressure (CPAP) may promote this pattern by increasing the proportion of E-E swallows [3-5], but their comparative effects in post-extubation patients remain unclear. Objectives: To compare the effects of nasal CPAP and HFNC on swallowing-breathing coordination patterns in post-extubation patients and to identify factors influencing this coordination Methods: This randomized, controlled, crossover trial includes patients who received invasive mechanical ventilation for ≥ 48 hours and were extubated within 48 hours prior to enrollment. Patients with dysphagia (modified water swallowing test score < 4) were excluded. Eligible patients are randomly assigned to Group A (CPAP → HFNC) or Group B (HFNC → CPAP). Each intervention is applied for 5 minutes, followed by three continuous water swallowing tests. Swallowing and respiratory phases are recorded using surface EMG and ECG-derived respiration. A 5-minute washout with low-flow nasal oxygen is provided between interventions. Swallowing–breathing coordination is classified into four patterns: E–E, I–E, E–I, and I–I. The primary outcome is the percentage of E-E swallows. Secondary outcomes include other patterns, swallowing frequency, expiratory time, and respiratory rate. All outcomes are analyzed using linear mixed-effects models. Hypothesis: CPAP and HFNC may differ in their effects on swallowing–breathing coordination, particularly in promoting the E–E pattern. Conclusion: This study explores how nasal CPAP and HFNC affect swallowing–breathing coordination and their potential impact on airway protection after extubation. Ethics and dissemination: Approved by the IRB, Faculty of Medicine, Chulalongkorn University. Results will be disseminated via peer-reviewed journals and conferences. Trial registration: TCTR20210607003